Off-shoring and productivity growth in the Italian manufacturing industries - Daveri, Francesco; Jona-Lasinio, Cecilia (Munich, 2008)
"We study the relation between the off-shoring of intermediates and services and productivity growth in the Italian manufacturing industries in 1995-2003. Our results indicate that the off-shoring of intermediates within the same industry (“narrow off-shoring”) is beneficial for productivity growth, while the off-shoring of services is not. We also find that the way in which off-shoring is measured may matter considerably. The positive relation between off-shoring of intermediates and productivity growth is there with our direct measures based on input-output data but disappears when either a broad measure or the Feenstra-Hanson off-shoring measure employed in other studies are used instead."